Procurement of Uniform Facilities And Infrastructure as Tourist Attraction For The Keranggan Rural Tourism, South Tangerang City - Rudy Pramono; Juliana Juliana (Journal of Community Service and Engagement, 2021)
Infrastructure plays an essential role in the tourism sector as a provider of facilities to tourist sites. This community service activity aims to procure uniforms and infrastructure facilities in the Karangan tourism village. This tourist village requires traditional Sundanese dance uniforms as mandatory equipment for every conventional dance performance. Art uniforms play an essential role in every performance because the audience will immediately see what clothes are worn by dancers or martial arts players. Comfortable and beautiful clothes will undoubtedly add to a good impression and show thorough preparation to add to the tourist attraction. The results of community service activities are expected to increase facilities and infrastructure, especially in the Procurement of uniforms as mandatory equipment for traditional dance performances that can add to the tourist attraction. Road conditions are essential in supporting tourism development, making it easier for visitors to access tourist sites and realize the expansion of entrepreneurship and creative tourism, making the Keranggan Tourism Village a superior product and destination tourism in South Tangerang City. The suggestion from participants that need to make Improvements to footpath infrastructure, wastewater irrigation, and clean water supply is essential for developing class tourist destinations, more highlighted the Sundanese culture, make the consistency and commitment and Kranggan village needs to provide several facilities to support the arts by procuring uniforms